PENGARUH DISIPLIN, ETOS KERJA, DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEGAWAI ADMINISTRATOR PELABUHAN TANJUNG PRIOK - Azhar Karim (Pusbindiklat - LIPI, 2010)
To the effect this research is subject to be know influence discipline, work ethic and Organizational Citizenship Behavior (OCB) staff Port Authority of Tanjung Priok. With gather primary and secondary data via observation, measuring instrument application, and documentation. Are method even analysis with Analysis’s tech bifilar Regression, at o by use of program SPSS. This observational result points out that after were done to test anova bifilar regression result significant by assesses F as big as 6.190 and significance 0.00. significance’s level point 0.00 inferior of point 0.05, so influence hypothesis is disciplined, work ethic and OCB significant on level 0.00, therefore Ha is accepted and Ho is refused, therefore discipline, work ethic and OCB staff Port Authority of Tanjung Priok at accepts. Matter this means independent variable influence(discipline, work ethic and the culture of organisation) to variable dependen OCB change is equal to 9,1%. Thus can be concluded that discipline, work ethic and influential OCB staff Port Authority of Tanjung Priok by assesses significance that acquired which is as big as 0,00, and is still lie under significance’s point 0,05,. Hereafter been disciplined ascendant job to OCB staff Port Authority of Tanjung Priok with significance 0,018, and is still lie under significance’s point 0,05,hence independent variable influence (Discipline) to variable dependen OCB change is equal to 5,5%. Influential work ethic to OCB staff Port Authority of Tanjung Priok with significance 0,009, and is still lie under significance’s point 0,05, hence independent variable influence (work ethic) to variable dependen OCB change is equal to 5,6%.. Culture job not ascendant to OCB staff Port Authority of Tanjung Priok with significance 0,809, one that is on significance’s point 0,05, hence independent variable influence (organizational culture) to variable dependen OCB change is equal to 1,6%.